2021
DOI: 10.3390/ijgi10030133
|View full text |Cite
|
Sign up to set email alerts
|

Spatiotemporal Analysis of COVID-19 Spread with Emerging Hotspot Analysis and Space–Time Cube Models in East Java, Indonesia

Abstract: In this research, we analyzed COVID-19 distribution patterns based on hotspots and space–time cubes (STC) in East Java, Indonesia. The data were collected based on the East Java COVID-19 Radar report results from a four-month period, namely March, April, May, and June 2020. Hour, day, and date information were used as the basis of the analysis. We used two spatial analysis models: the emerging hotspot analysis and STC. Both techniques allow us to identify the hotspot cluster temporally. Three-dimensional visua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
34
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(50 citation statements)
references
References 50 publications
(39 reference statements)
0
34
0
2
Order By: Relevance
“…A regional spatiotemporal understanding of COVID-19 is critical to provide insight into how the pandemic occurred and its continued growth and decline [10][11][12]. Previous studies by Purwanto et al [10] demonstrated that it is important to determine the spatial and temporal resolution of the STC model because it affects the detailed information on the endemic/epidemic, and it is important for the hotspot analysis results. Al-Kindi et al [11] also used the spatiotemporal assessment to determine the virus spread in Oman for 2 months.…”
Section: Introductionmentioning
confidence: 99%
“…A regional spatiotemporal understanding of COVID-19 is critical to provide insight into how the pandemic occurred and its continued growth and decline [10][11][12]. Previous studies by Purwanto et al [10] demonstrated that it is important to determine the spatial and temporal resolution of the STC model because it affects the detailed information on the endemic/epidemic, and it is important for the hotspot analysis results. Al-Kindi et al [11] also used the spatiotemporal assessment to determine the virus spread in Oman for 2 months.…”
Section: Introductionmentioning
confidence: 99%
“…In Indonesia, the first case of a Covid-19 infected person discovered in March 2020. The virus then transmitted through all the provinces in Indonesia, including East Java (Purwanto et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…However there were also neighboring areas that had relatively similar amount covid-19 confirmed cases like Probolinggo district with 2.213 confirmed cases and Pasuruan district 2.191 confirmed cases. This journal would find if there were significant clustering between East Java cities and districts covid-19 confirmed cases in year 2020 (Purwanto et al, 2021). The use spatial autocorrelation in this journal is to determine the mapping systematic spatial variation on confirmed cases of Covid-19 in East Java 2020 (Dhewantara et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…These restrictive measures have the same meaning as the three constraints in time geography to a certain extent [ 8 , 9 ]. Similarly, two important tools in time geography—space-time path and space-time prism—can also be used to simulate the spread of the COVID-19 pandemic [ 10 , 11 , 12 , 13 ]. The time-space path is often used to simulate the life trajectory of the coronavirus carrier, which can be used to find close contacts of the virus carrier [ 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%